The use of X‐shaped cross‐link in posterior spinal constructs improves stability in thoracolumbar burst fracture: A finite element analysis. Issue 9 (2nd May 2013) - Alizadeh, Mina; Kadir, Mohammed Rafiq Abdul; Fadhli, Miskon Mohd; Fallahiarezoodar, Ali; Azmi, Baharudin; Murali, Malliga Raman; Kamarul, Tunku
Abstract: Posterior instrumentation is a common fixation method used to treat thoracolumbar burst fractures. However, the role of different cross‐link configurations in improving fixation stability in these fractures has not been established. A 3D finite element model of T11‐L3 was used to investigate the biomechanical behavior of short (2 level) and long (4 level) segmental spine pedicle screw fixation with various cross‐links to treat a hypothetical L1 vertebra burst fracture. Three types of cross‐link configurations with an applied moment of 7.5 Nm and 200 N axial force were evaluated. The long construct was stiffer than the short construct irrespective of whether the cross‐links were used ( p < 0.05). The short constructs showed no significant differences between the cross‐link configurations. The XL cross‐link provided the highest stiffness and was 14.9% stiffer than the one without a cross‐link. The long construct resulted in reduced stress to the adjacent vertebral bodies and screw necks, with 66.7% reduction in bending stress on L2 when the XL cross‐link was used. Thus, the stability for L1 burst fracture fixation was best achieved by using long segmental posterior instrumentation constructs and an XL cross‐link configuration. Cross‐links did not improved stability when a short structure was used. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31:1447–1454, 2013